Raw data from the paper entitled "Deletion of the Wilms’ tumor suppressor gene in the cardiac troponin-T lineage reveals novel functions of WT1 in heart development" - Muñoz-Chápuli-Oriol, Ramón (Universidad de Málaga, 2021)
We performed a conditional ablation of Wt1 in the myocardium of mice embryos. RNASeq analysis identified differential expression of 137 genes in the E13.5 mutant heart as compared to controls. We provide raw data about the validation by qPCR of four of these genes as well as raw data about differences in proliferation and thickness of the ventricular myocardium. These raw data allowed for elaboration of the figures included in our paper entitled "Deletion of the Wilms’ tumor suppressor gene in the cardiac troponin-T lineage reveals novel functions of WT1 in heart development", published in Frontiers in Cell and Developmental Biology
Keywords: Enfermedad Cardiovascular; RNASeq; qPCR; Image analysis; Cardiac development